EFEKTIFITAS ROLLING MASSASE TERHADAP NYERI POST SECTIO CAESAREA (SC) - Sofina " "; Sri " Utami; Veny " Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Sectio Caesarea (SC) is a way of delivery a fetus by making incision on the front wall of the uterus through the abdomen. Physically this action will cause abdominal pain that comes from SC. The purpose of this research was to determine the effectiveness of rolling messase against SC’s pain. The design of this research was quasy experiment with non-equivalent control group which was divided into an experimental group and a control group. This research was conducted at the Petala Bumi Hospital in obstetrics room with a total sample were 34 respondents drawn using purposive sampling technique. Measuring instruments are observation’s sheet with numeric rating scale. The analysis used independent sample t test and dependent sample t test. The results showed the effect of rolling massase to SC’s pain in the experimental group after therapy with p value (0.000) < α (0.05). It’s means rolling massase effective in decreasing the intensity of pain by inhibiting the release of substances that can inhibit pain transmission, so that the pain is reduced. Based on the results, the study recommend to health workers especially nurse to provide nonpharmacological therapy such us rolling massase to reduce SC’s pain. Keywords: pain, post sectio caesarea, rolling massase